PENGARUH LATAR BELAKANG PENDIDIKAN, PENEMPATAN KERJA DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. MULTI MAS CHEMINDO - Hermina Puspa Indah Siagian; Yuli Arnida Pohan (Jurnal Widya, 2024)
This research aims to determine the influence of educational background, work placement and work experience on employee productivity at PT. Multi Mas Chemindo. In the research, the number of respondents used was 110 respondents. The data sources used in the research are secondary and primary data sources. The testing techniques used in the research are research instruments, descriptive statistical tests, classical assumption tests, multiple linear regression tests and research hypothesis tests. The data collection techniques used in this research used questionnaire data, literature, interviews and documentation. Based on the partial test results, it was found that educational background, work placement and work experience had a positive and significant effect on employee productivity at PT. Multi Mas Chemindo Medan. The results of this research simultaneously show that background variables, work placement and work experience together influence employee productivity.